2016
DOI: 10.1111/1755-5922.12172
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Safety of a Coordinated Delivery Tablet of Enteric‐Coated Aspirin 325 mg and Immediate‐Release Omeprazole 40 mg for Secondary Cardiovascular Disease Prevention in Patients at GI Risk

Abstract: SummaryIntroductionIn two, 6‐month, randomized, double‐blind Phase 3 trials, PA32540 (enteric‐coated aspirin 325 mg and immediate‐release omeprazole 40 mg) compared to aspirin alone was associated with fewer endoscopic gastric and duodenal ulcers in patients requiring aspirin therapy for secondary cardiovascular disease (CVD) prevention who were at risk for upper gastrointestinal (UGI) events.AimsIn this 12‐month, open‐label, multicenter Phase 3 study, we evaluated the long‐term cardiovascular and gastrointest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Of the 380 patients in the study, 292 completed the study. 8 Patients completed the study if they received PA32540 for at least 348 days. The 88 patients who did not finish the study reported the top reason for discontinuation to be adverse events (13.4%).…”
Section: Safetymentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 380 patients in the study, 292 completed the study. 8 Patients completed the study if they received PA32540 for at least 348 days. The 88 patients who did not finish the study reported the top reason for discontinuation to be adverse events (13.4%).…”
Section: Safetymentioning
confidence: 99%
“…6 Although there is astounding evidence on the use of ASA for the secondary prevention of cardiovascular events, adherence rates to this medication are varied and have been reported to be as low as 47% and as high as 72%. [7][8][9] The low adherence is often attributed to the gastrointestinal (GI) adverse effects associated with ASA. These effects include upper GI bleed, GI ulcers, gastroesophageal reflux disease (GERD), and dyspepsia.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations